PROGRAM DAYS FOR GIRLS SEBAGAI UPAYA PEMBERDAYAAN KOMUNITAS DAN AKSES KESEHATAN MENSTRUASI - Sapto Andriyono; Blenda Rahma Puspitasari; Nathania Trixie Marianus; Rifdhah Ayu Zakkiyah Rani; Aurellia Saraswati Winahyu Naiaputri; Afif Khuluqin Azhim (Jurnal Abdi Insani, 2026)
Menstruation is a natural biological process that is still often shrouded in stigma, limited access to sanitation, and a lack of reproductive health education. These conditions contribute to period poverty, which impacts women’s health, education, and well-being. The Days for Girls (DfG) program serves as a global initiative dedicated to improving access to menstrual health through an educational, sustainable, and community-empowerment-based approach. This article analyzes the implementation of Days for Girls activities as a service-learning model to enhance students’ understanding of menstrual health issues and women’s empowerment. The activities were conducted through a service-learning approach within the BBK International 6 Australia program at Days for Girls Bayswater, utilizing observation, interviews, and direct involvement in the preparation and distribution of menstrual kits. The activity outcomes demonstrate an increase in students’ understanding of period poverty, reproductive health, and the importance of sustainable menstrual hygiene management. Direct involvement in the production and preparation of menstrual kits also enhanced students’ social empathy, collaborative skills, and critical awareness of menstrual health issues as a global challenge. According to Days for Girls data, more than 192,000 menstrual kits have been distributed to over 60 countries, including 47,009 kits during the 2023–2024 period. The community-based approach is considered effective in reducing stigma, expanding access to menstrual health, and supporting the sustainable empowerment of women. The Days for Girls program effectively supports education, women’s empowerment, and sustainable community-based menstrual health awareness.